Nong Long Tai Song from Local Identity to Enhance Soft Power - Chuthap, Watsaranan (Journal of Social Sciences and Humanities Research in Asia, 2023)
The objective of the article is to study the song "Chuan Nong Long Tai" sung by Nat Rachen and Kluai Stamp on the issue of bringing vernacular identities to create songs and soft power. The result showed that "Chuan Nong Long Tai" song used southern identity in terms of words, southern idioms, melodies of Manohra poems, tourist attractions, folk traditions, and habits of the local people written as lyrics and melody.Soft power appears in 3 forms: 1) standstill acceptance, which can be seen from the large number of listeners listening to this song until it becomes a popular trend; 2) reproduction of songs by transforming them into popular cultural media; 3) the power to attract travelers to experience tourist attractions according to the song. Therefore, this song is a public relation tool that can reach a wide range of target groups. It helps to see ways to apply it as a business strategy and a guideline for applying social and cultural capitals for commercial use to create a creative economy.